2017
DOI: 10.1055/s-0042-117279
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Metabolic Syndrome: A Population-Based Thyroid Study

Abstract: The impact of thyroid dysfunction in subclinical ranges on metabolic syndrome (MetS) is not well known. The aim of the present study is to evaluate the association of thyroid dysfunction with MetS and its components. In the cross-sectional population-based Tehran Thyroid Study, out of 5 786 randomly selected participants, aged≥20 years, subjects with thyroid nodules and cancer or any severe systemic disease, those who were pregnant and those using thyroid medication were excluded, leaving 5 422 subjects to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 50 publications
1
45
1
2
Order By: Relevance
“…The study done by Mehran et al showed that some cases of Met S have thyroid abnormalities and mean TSH levels were higher in cases of Met S with sub clinical hypothyroidism as compared to Met S cases without sub clinical hypothyroidism [13]. This finding is very similar to our findings with larger sample size and more statistically significant results, however their study is cross-sectional and no assessment of endothelial dysfunction has been done.…”
Section: Discussionsupporting
confidence: 90%
“…The study done by Mehran et al showed that some cases of Met S have thyroid abnormalities and mean TSH levels were higher in cases of Met S with sub clinical hypothyroidism as compared to Met S cases without sub clinical hypothyroidism [13]. This finding is very similar to our findings with larger sample size and more statistically significant results, however their study is cross-sectional and no assessment of endothelial dysfunction has been done.…”
Section: Discussionsupporting
confidence: 90%
“…Thyroid hormones affect lipid and glucose metabolism, blood pressure, and obesity, all of which are associated with various cardiometabolic status [1][2][3]. Recent studies have demonstrated that the thyroid stimulating hormone (TSH) levels within the reference range were associated with obesity, lipid profile, and insulin resistance (IR) independent of thyroid function, which potentially modulates the cardiovascular conditions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Christy et al [51] found that HbA1c levels to be higher in patients with hypothyroidism, but this study included patients with anaemia. Other population-based studies have demonstrated the association between dysglycaemia and FT4 levels, but not with HbA1c levels [44,52]. Our study is the first community-based study that investigated the association of HbA1c levels with FT4 levels in euthyroid healthy subjects.…”
Section: Discussionmentioning
confidence: 64%